Studies on some bakery products fortified with barley and sorgum flour - EI-Sherlf, Sanaa A.; Kenawi, M. N. (2009)
The objective of this study was to see the effect of the incorporation of barley or sorghum on the physical , chemical and sensory charactristics of some bakery products ( cakes and biscuits ).
Includes reference.
Summary in Arabic.
1
Keywords: Baked products; Flour; Corn; Barley